Fluorine-free binder for positive electrode of lithium ion battery and preparation method thereof, positive electrode of battery and battery

By adopting a dual structure design in lithium-ion batteries, the core crosslinking structure combined with the outer oil-soluble shell layer is solved, and the problems of high swelling, low adhesion and insufficient toughness in lithium-ion batteries are solved. , achieving low swelling, high viscosity and high toughness, significantly improving the performance and stability of the battery.

CN118685137BActive Publication Date: 2024-12-24HUNAN GREEN POWER MATERIAL CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411188281.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-24
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

Existing fluorine-free binders have problems such as high swelling, low adhesion and insufficient toughness in lithium-ion batteries, resulting in poor battery energy density and cycle stability, and the crosslinked structure is prone to lead to extreme sheets during processing. Problems such as fracture and cracking.

Method used

The dual structure design is adopted for combining the core crosslinking structure with the outer oil-soluble shell layer. The mechanical strength and electrolyte resistance are improved through the crosslinking structure of the intermediate core, and the shell layer is polymerized in situ on the core to improve bonding performance and dispersion. , forming a "bolt rope structure" to reduce particle contact impedance.

Benefits of technology

It achieves excellent performance such as low swelling, high adhesion and high toughness, improves the performance and stability of the battery, reduces the volume changes and conductive agent coating problems of the electrode sheet during charging and discharging, and significantly improves the circulation of the battery. life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118685137B_ABST
    Figure CN118685137B_ABST
Patent Text Reader

Abstract

The present application provides a fluorine-free binder for positive electrode of lithium ion battery and a preparation method thereof, a positive electrode of battery and a battery. The structure of the fluorine-free binder for positive electrode of lithium ion battery comprises a cross-linked core and an oil-soluble shell. The cross-linked core is a spherical polymer with a cross-linked structure, and the oil-soluble shell is a polymer shell layer polymerized in situ on the cross-linked core, and one end of the molecular chain segment of the polymer in the shell layer is bound to the central cross-linked core; the binder raw material components comprise, by mass, 25-75 parts of A1 monomer, 25-50 parts of A2 monomer, 7-15 parts of cross-linked monomer, 20-50 parts of B1 monomer, 50-100 parts of B2 monomer, and 5-20 parts of functional monomer. The binder provided by the present application can alleviate the volume change of active material during charge and discharge, maintain the integrity of electrode structure, avoid excessive coating of active material and conductive agent by solution-type binder, thereby reducing contact impedance between particles and improving battery performance and stability. A preparation method of the binder, a positive electrode sheet and a battery are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion battery adhesives, and in particular to a fluorine-free adhesive for a lithium-ion battery positive electrode and a preparation method thereof, a battery positive electrode and a battery. Background Art

[0002] Traditional binders such as polyvinylidene fluoride (PVDF) contain fluorine, which not only increases costs but also may pollute the environment. Therefore, the development of fluorine-free binders has become an important research direction in the industry. When preparing lithium-ion batteries, the selection of binders needs to take into account their chemical properties, physical properties, and good compatibility with different positive electrode materials. In particular, the chemical properties of ternary positive electrode materials (such as NCA, NCM, etc.) are relatively active and easily react with water, so their stability in aqueous environments is poor. Therefore, organic solvent-based fluorine-free binders are more widely applicable than aqueous fluorine-free binders. Although some studies have attempted to develop organic solvent-based fluorine-free binders, these binders generally have problems such as high swelling, low adhesion, and insufficient toughness. These problems not only affect the energy density and cycle stability of the battery, but may also lead to reduced battery life and safety hazards.

[0003] During the use of current organic solvent-based fluorine-free binders, the binder will be coated on the surface of active particles in large quantities. The organic polymer itself does not have excellent conductivity. When used as a binder and completely wrapping the positive electrode material, it will hinder the transmission of electrons and ions in the positive electrode to a certain extent, resulting in an increase in the contact impedance between particles and an increase in the polarization of battery charge and discharge, which will weaken the battery's cycle performance. At the same time, the existing binders are not tolerant enough to the electrolyte, and will interact with the ions or solvent molecules in the electrolyte, causing swelling, resulting in changes in the binder's performance. At present, the main method to solve the problem of binder tolerance to electrolytes is to introduce a cross-linked structure to inhibit swelling, but the cross-linked binder may deteriorate the solubility, resulting in uneven distribution of the binder in the electrode, which in turn causes the electrode to peel off or break during the charge and discharge process. When the cross-linking density is too large, the polymer becomes hard and brittle, resulting in the battery electrode being prone to breakage and cracking during processing.

[0004] Therefore, adjusting the chemical structure and formula of the binder and developing a fluorine-free oily binder for the positive electrode with excellent properties such as low swelling, high adhesion and high toughness has become an important demand of the current industry. Summary of the invention

[0005] The technical problem to be solved by the present application is to overcome the deficiencies and defects mentioned in the above background technology, to solve the problems of uneven distribution of cross-linked modified binders in pole pieces and easy breakage and cracking during processing to a certain extent, and to provide a fluorine-free oil-soluble positive electrode binder with a double structure of core cross-linking and shell oil-soluble and a preparation method thereof, a battery positive electrode and a battery.

[0006] In order to solve the above technical problems, the technical solution proposed in this application is:

[0007] In a first aspect, a fluorine-free binder for a positive electrode of a lithium-ion battery comprises a middle core and an outer oil-soluble shell, wherein one end of a molecular chain segment of the outer oil-soluble shell is bound to the middle core, and the middle core is a cross-linked structure;

[0008] The raw material components include, by mass: 25-75 parts of A1 monomer, 25-50 parts of A2 monomer, 7-15 parts of cross-linking monomer, 20-50 parts of B1 monomer, 50-100 parts of B2 monomer, and 5-20 parts of functional monomer.

[0009] The fluorine-free binder for the positive electrode of the lithium-ion battery of the present application has a stable structure due to the special cross-linked structure design of the middle core part, so as to improve the mechanical strength of the binder and the tolerance of the binder in the electrolyte.

[0010] Then a shell layer is in situ polymerized on the middle core. The shell layer has good compatibility with the organic solvent NMP (N-methylpyrrolidone), which makes the material soluble and dispersible under the conditions of organic solvents. The shell layer can provide good bonding properties for the binder, which can alleviate the volume change of the active material during the charging and discharging process and maintain the integrity of the electrode structure. At the same time, it avoids excessive coating of the active material and the conductive agent by the solution-type binder, reduces the contact impedance between the particles, and improves the performance and stability of the battery.

[0011] In a second aspect, the present application also provides a method for preparing a fluorine-free binder for a positive electrode of a lithium ion battery, comprising the following steps:

[0012] S1. Preparing a core emulsion in advance: After the emulsifier and deionized water are stirred and dissolved, A1 monomer, A2 monomer and cross-linking monomer are added and stirred, pre-emulsified, stirred and heated, and then an initiator is added to react to obtain a first core emulsion (the initiator can also be added in the pre-emulsification step);

[0013] S2, preparing a transition layer: adding a crosslinking monomer and an initiator dropwise to the first core emulsion obtained in step S1 to obtain a second core emulsion with an olefinic transition layer;

[0014] S3, preparing a shell solution: mixing the B1 monomer, the B2 monomer, and the functional monomer to obtain a shell solution;

[0015] S4, adding the shell solution and the initiator solution obtained in step S3 dropwise to the second core emulsion obtained in step S2, and reacting at the same temperature to obtain a preliminary emulsion;

[0016] S5. Filter and dry the preliminary emulsion obtained in step S4 to obtain a solid powder, which is a fluorine-free binder for the positive electrode of a lithium-ion battery.

[0017] In a third aspect, the present application also provides a lithium-ion battery positive electrode, which includes the lithium-ion battery positive electrode fluorine-free binder as described in the first aspect, or the lithium-ion battery positive electrode fluorine-free binder obtained by the preparation method as described in the second aspect, and also includes a current collector and a positive electrode active coating coated on the surface of the current collector.

[0018] In a fourth aspect, the present application also provides a lithium-ion soft-pack battery, wherein the lithium-ion battery comprises the above-mentioned lithium-ion battery positive electrode.

[0019] It can be understood that the beneficial effects of the second to fourth aspects mentioned above can be found in the relevant description of the first aspect mentioned above, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0021] Figure 1 is a schematic diagram of the preparation of the core emulsion transition layer;

[0022] Figure 2 is a schematic diagram of the preparation of the in-situ coating emulsion;

[0023] Figure 3 It is a schematic diagram of the structure of the fluorine-free binder of the positive electrode of the lithium-ion battery after being dissolved in the NMP solvent;

[0024] Figure 4 is a SEM image of the core emulsion of Example 1;

[0025] Figure 5 is the SEM image of the emulsion after in-situ coating in Example 1;

[0026] Figure 6 is a SEM image of the binder prepared in Example 1 after being dissolved in NMP;

[0027] Figure 7 yes Figure 6 A partial enlarged view of . DETAILED DESCRIPTION

[0028] To facilitate the understanding of the present application, the present application will be described in more comprehensive and detailed manner below in conjunction with the accompanying drawings and preferred embodiments of the specification, but the protection scope of the present application is not limited to the following specific embodiments.

[0029] Unless otherwise defined, all professional terms used below have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this application.

[0030] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0031] The present application provides a fluorine-free binder for positive electrode of lithium ion battery, the structure of which includes a middle core and an outer oil-soluble shell, one end of the molecular chain segment of the outer oil-soluble shell is bound to the middle core, and the middle core is a cross-linked structure;

[0032] The raw material components include, by mass: 25-75 parts of A1 monomer, 25-50 parts of A2 monomer, 7-15 parts of cross-linking monomer, 20-50 parts of B1 monomer, 50-100 parts of B2 monomer, and 5-20 parts of functional monomer.

[0033] In some embodiments, the A1 monomer is a soft monomer of a long-chain olefin containing an unsaturated carbon-carbon double bond, the A2 monomer is a hard monomer, the B1 monomer is a solubilizing monomer, and the B2 monomer is a soft monomer of a long-chain olefin containing an unsaturated carbon-carbon double bond; the functional monomer is a carboxylic acid monomer or a sulfonic acid monomer with a carbon-carbon double bond.

[0034] The fluorine-free binder for the positive electrode of the lithium-ion battery of the present application has a stable structure due to the special cross-linked structure design of the middle core part, so as to improve the mechanical strength of the binder and the tolerance of the binder in the electrolyte.

[0035] Then, a shell layer is in-situ polymerized on the middle core. The shell layer has good compatibility with the organic solvent NMP (N-methylpyrrolidone), so that the material has solubility and dispersibility under the conditions of organic solvents, and the shell layer can provide good bonding properties for the adhesive.

[0036] The special cross-linked structure is designed as follows: when NMP is used, the dissolution mechanism of this double-layer structure in the solution can be regarded as a "tethered rope structure" model, in which after the binder is dissolved in the solvent, the cross-linked middle core swells to a limited extent, one end of the outer shell molecular segment is bound to the middle core, and the other end stretches in the solvent, and the stretching of the binder outer shell is equivalent to a rope, and the binder core is equivalent to a tether, forming a "tethered rope structure".

[0037] The "plug" corresponds to the middle core of the cross-linked structure, which can provide excellent mechanical strength structure. Each point on the middle core of the cross-linked structure can withstand greater force, which helps to alleviate the volume change of the battery electrode during the charge and discharge process and maintain the integrity of the electrode structure. At the same time, due to the role of the core and shell segments, it has a certain restraining effect on the complete dissolution of the outer shell segments, avoiding the problem of complete coverage of the conductive agent and the active substance by the polymer, and retaining a certain gap between the conductive agent and the active substance, which is conducive to the penetration of the electrolyte and the transmission of ions, reducing the contact impedance between the particles and ensuring the battery performance.

[0038] The "rope" corresponds to the oil-soluble shell. During the dissolution process, one end of the shell molecular chain stretches in the solvent, providing good adhesion and cohesion for the binder. At the same time, due to the binding effect of the core, the problem of complete coverage of the conductive agent and active material by the polymer is avoided, which can reduce the contact impedance between the particles, ensure the battery performance, and make the battery have the characteristics of low swelling, high cohesion, high toughness, etc.

[0039] Based on the general inventive concept, the present application also provides a method for preparing a fluorine-free binder for a positive electrode of a lithium-ion battery, comprising the following steps:

[0040] S1, preparing a core emulsion: stirring and dissolving an emulsifier and deionized water, adding A1 monomer, A2 monomer, and crosslinking monomer, stirring, pre-emulsifying, stirring and heating, and then adding an initiator to react to obtain a first core emulsion;

[0041] S2, preparing a transition layer: adding a crosslinking monomer and an initiator dropwise to the first core emulsion obtained in step S1 to obtain a second core emulsion with an olefinic transition layer;

[0042] S3, preparing a shell solution: mixing the B1 monomer, the B2 monomer, and the functional monomer to obtain a shell solution;

[0043] S4, adding the shell solution and the initiator solution obtained in step S3 dropwise to the second core emulsion obtained in step S2, and reacting at the same temperature to obtain a preliminary emulsion;

[0044] S5, filtering and drying the preliminary emulsion obtained in step S4 to obtain a solid powder, which is a fluorine-free binder for the positive electrode of a lithium-ion battery.

[0045] Step S1 of this embodiment can also be: the initiator is added in the pre-emulsification step, and then stirred and heated to react to obtain the first core emulsion.

[0046] In some embodiments, the present application also provides a method for preparing a fluorine-free binder for a positive electrode of a lithium-ion battery, further comprising the following steps:

[0047] S1, preparing a core emulsion: stirring and dissolving 1 / 3 of an emulsifier and deionized water, adding A1 monomer, A2 monomer, and a cross-linking monomer, stirring, pre-emulsifying, stirring and heating, and then adding an initiator to react to obtain a first core emulsion;

[0048] S2, preparing a transition layer: adding a mixed emulsion made of a crosslinking monomer, water and an emulsifier to the first core emulsion obtained in step S1 to obtain a second core emulsion with an olefinic transition layer;

[0049] S3, preparing a shell solution: mixing B1 monomer, B2 monomer, and functional monomer with water and an emulsifier to prepare a shell emulsion;

[0050] S4, adding the shell emulsion and the initiator solution obtained in step S3 dropwise to the second core emulsion obtained in step S2, and reacting at the same temperature to obtain a preliminary emulsion.

[0051] This embodiment adopts a method of adding emulsifier multiple times, and the rest is the same as the above scheme.

[0052] In some embodiments, the emulsifier in step S1 is a combination of one or more of calcium dodecyl benzoate, sodium dodecyl sulfonate, sodium dodecyl sulfate, SR-10, SE-10, SN-10 and OP-10;

[0053] The A1 monomer is a soft monomer of a long-chain olefin containing an unsaturated carbon-carbon double bond, and contains one unsaturated carbon-carbon double bond. The soft monomer of the long-chain olefin includes a monomer composed of 5 to 100 carbon atoms and other heteroatoms. The A1 monomer includes a combination of one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl methacrylate, isodecyl methylpropionate, amyl acrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, ethoxyphenol acrylate, ethoxynonylphenol acrylate, tetrahydrofurfuryl methacrylate, diethylene glycol monoethyl ether acrylate, and methoxypolyethylene glycol methacrylate; its function is to provide good toughness for the core.

[0054] The A2 monomer is a hard monomer, and the A2 monomer includes one or more of methyl acrylate, methyl methacrylate, acrylonitrile, methacrylonitrile, styrene, vinyl pyrrolidone and acrylamide. Its function is to increase the cohesive strength, improve the cohesive force of the adhesive core and the tolerance to the electrolyte.

[0055] In some embodiments, the crosslinking monomer is an olefin monomer containing multiple unsaturated carbon-carbon double bonds, the number of carbon-carbon double bonds is ≥ 2, and the crosslinking monomer includes a combination of one or more of 1,6-hexanediol diacrylate, ethylene oxide diacrylate, ethoxylated bisphenol A diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate. Its function is to form a crosslinked structure, inhibit the dissolution of the core in NMP, and improve the tolerance to the electrolyte.

[0056] In some embodiments, the amount of A1 monomer added in step S1 is 25-75 parts, the amount of A2 monomer added is 25-50 parts, the amount of cross-linking monomer added is 2-5 parts, the amount of emulsifier added is 0.5%-2.5% of the amount of monomer, the amount of initiator added is 0.5%-2% of the amount of monomer, the amount of deionized water is 4-9 times the sum of the mass parts of A1 monomer, A2 monomer and cross-linking monomer, and the pre-emulsification in step S1 is 30min-50min.

[0057] In some embodiments, in step S1, the temperature is raised to 55-85° C. with stirring and the reaction is carried out for 2-6 hours. The particle size of the core emulsion is 20-500 nm. By adjusting the ratio of A1 monomer, A2 monomer, and cross-linking monomer, the particle size and distribution state of the product when dissolved in NMP, as well as the tolerance of the binder in the electrolyte can be controlled.

[0058] In some embodiments, the amount of cross-linking monomer added in step S2 is 5-10 parts, and the initiator is 0.5%-2% of the amount of cross-linking monomer. After the dropwise addition in step S2, the mixture is stirred and heated to 55-85°C and reacted for 2-6 hours, and the particle size (D50) of the second core emulsion is 20-510 nm.

[0059] The cross-linking monomer in step S2 is similar to the cross-linking monomer in step S1, both of which are olefin monomers containing multiple unsaturated carbon-carbon double bonds, and the number of carbon-carbon double bonds is ≥2. The cross-linking monomer is a combination of one or more of 1,6-hexanediol diacrylate, ethylene oxide diacrylate, ethoxylated bisphenol A diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate, and its function is to modify the core surface so that its surface has a partial double bond structure, so that the shell layer can grow in situ on the core layer surface.

[0060] In some embodiments, the initiator is a combination of one or more of sodium persulfate, potassium persulfate, ammonium persulfate and azobisisobutylamidine hydrochloride, and the volume ratio of the initiator to deionized water is 1: (7-10).

[0061] In some embodiments, the B1 monomer in step S3 is a solubilizing monomer, and the B1 monomer includes a combination of one or more of acrylonitrile, methacrylonitrile, styrene and vinyl pyrrolidone; its function is to increase the solubility of the shell in NMP, the cohesive strength and the tolerance to the electrolyte.

[0062] The B2 monomer is a soft monomer of a long-chain olefin containing an unsaturated carbon-carbon double bond, containing one unsaturated carbon-carbon double bond. The long-chain olefin monomer includes a monomer composed of 5 to 100 carbon atoms and other heteroatoms. The B2 monomer includes a combination of one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl methacrylate, isodecyl methylpropionate, amyl acrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, ethoxyphenol acrylate, ethoxynonylphenol acrylate, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, diethylene glycol monoethyl ether acrylate, and methoxypolyethylene glycol methacrylate; its function is to provide the adhesive with good flexibility and bonding properties.

[0063] In some embodiments, the functional monomer in step S3 is a carboxylic acid / sulfonic acid monomer with a carbon-carbon double bond, which is a combination of one or more of acrylic acid, sodium acrylate, lithium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, β-acryloxypropionic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium allyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate and sodium styrene sulfonate, and its function is to improve the ionic conductivity of the binder.

[0064] The thickness of the shell is controlled by the shell components. If the thickness is too thin, the electrode will not be tough enough. If it is too thick, the viscosity of the slurry will increase and the processing solid content will decrease.

[0065] In some embodiments, the added amount of the B1 monomer is 20-50 parts, the added amount of the B2 monomer is 50-100 parts, and the added amount of the functional monomer is 5-20 parts.

[0066] In some embodiments, the dripping in step S4 is for 0.3h~2h, the heat preservation reaction is 55°C~85°C, and the reaction is for 1h~8h; the filtration in step S5 is through a 200-mesh filter bag, and the drying method is not limited.

[0067] Based on the general inventive concept, the present application also provides a lithium ion battery positive electrode made from the above-mentioned lithium ion battery positive electrode fluorine-free binder, the lithium ion battery positive electrode comprising a current collector and a positive electrode active coating coated on the surface of the current collector.

[0068] Based on the general inventive concept, the present application also provides a lithium-ion soft-pack battery, which includes the above-mentioned lithium-ion battery positive electrode.

[0069] Embodiment 1:

[0070] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0071] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0072] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0073] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0074] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0075] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0076] S5. Filter the product emulsion obtained in step S4, and then spray dry it to obtain a solid powder which is a fluorine-free binder for the positive electrode of a lithium-ion battery.

[0077] Figure 1 It is a schematic diagram of the preparation of the nuclear emulsion transition layer of the present application;

[0078] Figure 2 It is a schematic diagram of the preparation of the in-situ coating emulsion of the present application;

[0079] Figure 3 It is a schematic diagram of the structure of the fluorine-free binder for the positive electrode of the lithium-ion battery of the present application after being dissolved in the NMP solvent. When used, the binder of the present application includes a core and an oil-soluble shell. The core is a spherical polymer with a cross-linked structure, and the oil-soluble shell is a polymer shell layer in situ polymerized on the core, and one end of the molecular chain segment of the polymer in the shell layer is bound to the central cross-linked core;

[0080] Figure 4 is a SEM image of the core emulsion of Example 1;

[0081] Figure 5 This is the SEM image of the emulsion after in-situ coating in Example 1. It can be seen that the shell layer still maintains a good core-shell structure;

[0082] Figure 6 : This is a SEM image of the binder prepared in Example 1 after being dissolved in NMP. It can be seen that the shell of the binder is dissolved under the action of NMP, and the molecular chains are entangled with each other during the drying process. No obvious structure can be seen in the electron microscope image, but the core can only swell to a limited extent. Some circular protrusions can be seen in the electron microscope image. The local enlarged image at A is shown in FIG. Figure 7 .

[0083] Embodiment 2:

[0084] The difference between Example 2 and Example 1 is that the core composition is changed.

[0085] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0086] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0087] S1, preparing a core emulsion: stirring and dissolving 0.5g of emulsifier SR-10 and 800g of deionized water, adding 25g of methyl methacrylate, 75g of isooctyl acrylate, and 3.5g of a cross-linking monomer ethoxylated trimethylolpropane triacrylate, stirring, pre-emulsifying, stirring and heating to 75°C, and then dropping 1g of ammonium persulfate solution and reacting for 3h to obtain a first core emulsion;

[0088] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer, ethoxylated trimethylolpropane triacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0089] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0090] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0091] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is the fluorine-free binder for the positive electrode of a lithium ion battery.

[0092] Embodiment 3:

[0093] The difference between the present embodiment 3 and the embodiment 1 is that the core composition ratio is changed.

[0094] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0095] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0096] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 50 g of acrylonitrile, 50 g of butyl acrylate, and 5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0097] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0098] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0099] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0100] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is the fluorine-free binder for the positive electrode of a lithium ion battery.

[0101] Embodiment 4:

[0102] The difference between the fourth embodiment and the first embodiment is that the components of the shell are controlled.

[0103] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0104] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0105] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0106] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0107] S3, preparing a shell solution: mixing 50 g of vinyl pyrrolidone, 40 g of isooctyl acrylate, and 10 g of sodium p-styrene sulfonate;

[0108] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0109] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is the fluorine-free binder for the positive electrode of a lithium ion battery.

[0110] Embodiment 5:

[0111] The difference between the present embodiment 5 and the embodiment 1 is that the proportion of the components of the shell is controlled.

[0112] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0113] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0114] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0115] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0116] S3, preparing a shell solution: mixing 20 g of acrylonitrile, 60 g of butyl acrylate and 20 g of acrylic acid;

[0117] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0118] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is a fluorine-free binder for the positive electrode of a lithium-ion battery.

[0119] Embodiment 6:

[0120] The difference between this embodiment 6 and embodiment 1 is that the ratio of the shell layer to the core layer is changed, and the shell layer is larger than that of the basic embodiment 1, and the flexibility is strong, but the viscosity of the glue is relatively large.

[0121] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0122] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0123] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0124] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0125] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 100 g of butyl acrylate and 15 g of acrylic acid;

[0126] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0127] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is the fluorine-free binder for the positive electrode of a lithium ion battery.

[0128] Embodiment 7:

[0129] The difference between Example 7 and Example 1 is that the transition layer composition is changed, and the effect is the same. A method for preparing a fluorine-free binder for a positive electrode of a lithium ion battery comprises the following steps:

[0130] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0131] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0132] S2, preparing a transition layer: after completing the above steps, 5 g of a crosslinking monomer trimethylolpropane triacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0133] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0134] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0135] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is the fluorine-free binder for the positive electrode of a lithium ion battery.

[0136] Embodiment 8:

[0137] The difference between Example 8 and Example 1 is that the reaction conditions are changed.

[0138] A method for preparing a fluorine-free binder for a lithium-ion battery positive electrode comprises the following steps:

[0139] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0140] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 85° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0141] S2, preparing a transition layer: after completing the above steps, 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution are added dropwise while the solution is still hot for 0.5 h, and the reaction is continued at the temperature for 1 h to obtain a second core emulsion with an olefinic transition layer;

[0142] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0143] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 85°C for 2 hours. After the addition is complete, the reaction is continued at a constant temperature of 2 hours to obtain a product emulsion;

[0144] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is the fluorine-free binder for the positive electrode of a lithium ion battery.

[0145] Comparative Example 1:

[0146] The difference between this comparative example 1 and example 1 is that no cross-linking agent is added during the core reaction, the core swells greatly, and its swelling effect in the electrolyte cannot be suppressed.

[0147] A method for preparing a lithium ion battery binder comprises the following steps:

[0148] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0149] S1. Prepare a nuclear emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile and 75 g of butyl acrylate, stir and pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a nuclear emulsion;

[0150] S2, preparing a transition layer: after completing the above steps, add 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution while hot for 0.5 h, and continue to keep warm for 1 h to obtain a core emulsion with an olefinic transition layer;

[0151] S3, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0152] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0153] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is a lithium-ion battery binder.

[0154] Comparative Example 2:

[0155] The difference between this comparative example 2 and example 1 is that the directly cross-linked core emulsion has no subsequent steps and cannot be dissolved in the NMP solvent after drying.

[0156] A method for preparing a lithium ion battery binder comprises the following steps:

[0157] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0158] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a core emulsion;

[0159] S2. The product emulsion obtained in step S2 is filtered and then spray-dried to obtain a solid powder, which is a lithium-ion battery binder.

[0160] Comparative Example 3:

[0161] The difference between Comparative Example 3 and Example 1 is that no transition layer is added and the film swells too much.

[0162] A method for preparing a lithium ion battery binder comprises the following steps:

[0163] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0164] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a first core emulsion;

[0165] S2, preparing a shell solution: mixing 50 g of acrylonitrile, 40 g of butyl acrylate and 10 g of acrylic acid;

[0166] S3, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. for 2 h. After the addition is complete, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0167] S4, filtering the product emulsion obtained in step S3, and then drying to obtain a solid powder, which is a lithium-ion battery binder.

[0168] Comparative Example 4:

[0169] Compared with Example 1, the amount of shell solution used in Comparative Example 4 is insufficient, resulting in a small shell layer and insufficient flexibility.

[0170] A method for preparing a lithium ion battery binder comprises the following steps:

[0171] An initiator solution is prepared in advance by mixing initiator ammonium persulfate and deionized water in a ratio of 1:9 to form an initiator solution;

[0172] S1. Prepare a core emulsion: stir and dissolve 0.5 g of emulsifier SR-10 and 800 g of deionized water, add 25 g of acrylonitrile, 75 g of butyl acrylate, and 3.5 g of a cross-linking monomer 1,6-hexanediol diacrylate, stir, pre-emulsify, stir and heat to 75° C., then dropwise add 1 g of ammonium persulfate solution and react for 3 h to obtain a core emulsion;

[0173] S2, preparing a transition layer: after completing the above steps, add 10 g of a crosslinking monomer 1,6-hexanediol diacrylate and 0.1 g of an ammonium persulfate solution while hot for 0.5 h, and continue to keep warm for 1 h to obtain a core emulsion with an olefinic transition layer;

[0174] S3, preparing a shell solution: mixing 25 g of acrylonitrile, 20 g of butyl acrylate and 5 g of acrylic acid;

[0175] S4, preparing a shell layer; dropping the shell layer solution obtained in step S3 and 1 g of ammonium persulfate solution into the core emulsion obtained in step S2 to react at a constant temperature of 75° C. The dropping time is 2 h. After the dropping is completed, the reaction is continued at a constant temperature of 2 h to obtain a product emulsion;

[0176] S5. Filter the product emulsion obtained in step S4, and then spray-dry to obtain a solid powder, which is a lithium-ion battery binder.

[0177] Embodiment 9:

[0178] Application of a fluorine-free positive electrode binder material:

[0179] Since the binders in Comparative Examples 1 to 3 had obvious defects, no soft-pack batteries were prepared for evaluation.

[0180] Examples 1 to 7 and commercially available PVDF positive and negative electrode slurries and pole pieces and their soft-pack batteries were prepared according to the following method:

[0181] (I) Preparation of positive electrode slurry and electrode sheet: including but not limited to the following preparation methods:

[0182] The positive electrode fluorine-free binder material prepared in the present application is prepared into a binder glue solution with a solid content of 5wt% and NMP (N-methylpyrrolidone) solution, and then the positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O 2 After the conductive agent Super-Li, the conductive agent CNT and the configured binder glue are fully dispersed and mixed according to the solid content of 97:1.5:0.5:1, the solvent NMP is added to adjust the solid content to 65%, and then the mixed slurry is filtered through a 200-mesh screen and evenly coated on both sides of the aluminum foil. After drying, rolling and cutting, the required positive electrode sheet is obtained. The surface density of the positive electrode active layer is 35.5mg / cm 2 , compacted density is about 3.3g / cm 3 .

[0183] (II) Preparation of negative electrode slurry and electrode sheet: including but not limited to the following preparation methods:

[0184] The negative electrode active material graphite, conductive agent Super-Li, binder SBR and dispersant CMC were added to the deionized water solvent in a ratio of 97.8:0.4:1.2:0.6 to adjust the solid content to 50%, and fully stirred to obtain a mixed slurry. The mixed slurry was then filtered with a 200-mesh screen and evenly coated on a copper foil. The desired negative electrode sheet was obtained after drying, rolling and cutting. The surface density of the negative electrode sheet was about 16.0 mg / cm 2 , compacted density is about 1.5g / cm 3 .

[0185] The diaphragm uses a PE porous polymer film with a thickness of 20 μm as the isolation membrane.

[0186] Ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC) were mixed evenly in a mass ratio of 3:5:2, and then the electrolyte lithium salt LiPF 6 The electrolyte was obtained by dissolving 1 mol / L in the above-prepared solvent.

[0187] (III) Preparation of lithium-ion batteries: The positive electrode sheet, negative electrode sheet and separator are wound, and then subjected to processes such as welding, baking, liquid injection, packaging, formation and capacity division to obtain an experimental soft-pack battery cell.

[0188] Test method:

[0189] 1. Electrolyte resistance performance:

[0190] The swelling method was used to test the electrolytic resistance of the adhesive. The specific method was to make the adhesive into a 4cm*2cm*0.02cm adhesive film, and then immerse it in the above-configured electrolyte at 65°C for 3 days and 7 days. After immersion, the adhesive was taken out and the residual electrolyte on the surface was gently wiped off. The volume and mass were tested and the changes before and after immersion were compared. The results are shown in Table 1.

[0191] Volume growth rate = (volume after immersion in electrolyte - volume before immersion in electrolyte) / volume before immersion in electrolyte × 100%.

[0192] Mass increase rate = (mass after immersion in electrolyte - mass before immersion in electrolyte) / mass before immersion in electrolyte × 100%.

[0193] 2. Viscosity test:

[0194] Use a kinematic viscometer to measure the viscosity of rubber and slurry. Take a certain amount of sample in the sample cup, slowly immerse the rotor into the sample, and then connect the viscometer host and water bath system. Start the measurement after the sample temperature stabilizes at 25°C. The test time is 120s, the data collection interval is 20s, and a total of 6 data points are collected. The average value of the measurement is the viscosity of the test sample. The results are shown in Table 2.

[0195] 3. Pole flexibility:

[0196] The test was conducted using a cylindrical shaft bending tester. The specific method was to cut the pole piece into a 2cm*15cm rectangular strip, then wind it onto a metal cylinder with a diameter of 2mm, and slowly pull it 180° to observe whether the pole piece had cracks or powder loss. The flexibility of the pole piece was determined by observing whether there were cracks or powder loss on the surface of the pole piece. If there were no cracks or powder loss, it was good; if there were cracks or powder loss, it was poor. The results are shown in Table 2.

[0197] 4. Pole diaphragm resistance: The pole diaphragm resistance was tested using a two-probe method. The results are shown in Table 2.

[0198] 5. Peeling force: Use a tensile tester to test the bonding force between the membrane and the current collector. First, stick the 3M special peeling tape on the stainless steel plate, and then stick the electrode on the tape. The tensile machine clamps the electrode for 180° peeling. The stroke speed is 100mm / min. The test data is judged by the average value of the stable period. The results are shown in Table 2.

[0199] 6. Electrochemical cycle stability: The prepared soft-pack test battery was subjected to an electrochemical cycle performance test of constant current and constant voltage charge and discharge at 25°C. First, it was charged to 4.3V at 0.5C, left for 30 minutes, and then discharged to 2.5V at different rates, and then left for 30 minutes. The above steps were repeated for 500 cycles, and the test discharge rates were 0.5C and 2C. The results are shown in Table 3.

[0200] Capacity attenuation rate after 500 cycles = (1st cycle capacity - 500th cycle capacity) / 1st cycle capacity × 100%.

[0201] The prepared positive electrode slurry, positive electrode sheet and experimental soft pack battery were tested, and the obtained data are as follows:

[0202]

[0203] *Comparative Example 2 could not be dissolved in NMP after drying, so it was not possible to prepare a film to measure its electrolyte resistance.

[0204]

[0205]

[0206] It can be seen from the above embodiments and comparative examples that the electrolyte resistance of the binder prepared in the present application is the result of the combined effect of the intermediate core, transition layer and oil-soluble shell of the cross-linked structure. When the intermediate core is missing, the binder cannot inhibit the solvation of the electrolyte due to the lack of a structural inner core. During the electrolyte immersion process, the molecular chains creep and diffuse, and the swelling reaches 200%. In the absence of a transition layer, the outer shell cannot be grafted onto the intermediate core, and excessive swelling also occurs. The binder of the present application can effectively control the swelling caused by volume change due to its special "tether structure" (i.e., the combination of the intermediate core and the outer oil-soluble shell).

[0207] After the outer oil-soluble shell is dissolved in the solvent, one end of its molecular chain segment stretches in the solvent to form a strong bonding network, which enhances the bonding force with the active substance and the conductive agent. The peeling force is significantly improved compared with PVDF. At the same time, due to the constraint of the core, excessive coating of the active substance and the conductive agent is avoided, the contact efficiency between the particles is improved, the contact impedance is reduced, and the diaphragm resistance of the electrode is significantly reduced.

[0208] By conducting comparative experiments (cycle life test) with the mainstream binder PVDF on the market, it can be clearly demonstrated that the binder of the present application has a significant effect in improving the cycle life performance of the battery.

[0209] In summary, the binder of the present application, with its unique structural design, exhibits the characteristics of low swelling, high adhesion, high toughness, etc. in the battery field, significantly improving the performance and stability of the battery.

Claims

1. A fluorine-free binder for positive electrode of lithium ion battery, characterized in that: The intermediate core and the outer oil-soluble shell are two parts, one end of the molecular chain segment of the outer oil-soluble shell is bound to the intermediate core, and the intermediate core is a cross-linked structure; The raw material components include, by mass: 25-75 parts of A1 monomer, 25-50 parts of A2 monomer, 7-15 parts of cross-linking monomer, 20-50 parts of B1 monomer, 50-100 parts of B2 monomer, and 5-20 parts of functional monomer. The A1 monomer is a soft monomer of a long-chain olefin containing an unsaturated carbon-carbon double bond, the A2 monomer is a hard monomer, the B1 monomer is a solubilizing monomer, and the B2 monomer is a soft monomer of a long-chain olefin containing an unsaturated carbon-carbon double bond; the functional monomer is a carboxylic acid monomer or a sulfonic acid monomer with a carbon-carbon double bond. The method for preparing the fluorine-free binder for the positive electrode of a lithium ion battery comprises the following steps: S1, preparing a core emulsion: stirring and dissolving an emulsifier and deionized water, adding A1 monomer, A2 monomer, and crosslinking monomer, stirring, pre-emulsifying, stirring and heating, and then adding an initiator to react to obtain a first core emulsion; S2, preparing a transition layer: adding a crosslinking monomer and an initiator dropwise to the first core emulsion obtained in step S1 to obtain a second core emulsion with an olefinic transition layer; S3, preparing a shell solution: mixing the B1 monomer, the B2 monomer, and the functional monomer to obtain a shell solution; S4, adding the shell solution and the initiator solution obtained in step S3 dropwise to the second core emulsion obtained in step S2, and reacting at the same temperature to obtain a preliminary emulsion; S5, filtering and drying the preliminary emulsion obtained in step S4 to obtain a solid powder, which is a fluorine-free binder for the positive electrode of a lithium-ion battery; The A1 monomer consists of 5 to 100 carbon atoms and other heteroatoms, and the A1 monomer includes one or more combinations of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl methacrylate, isodecyl methylpropionate, amyl acrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, ethoxyphenol acrylate, ethoxynonylphenol acrylate, tetrahydrofurfuryl methacrylate, diethylene glycol monoethyl ether acrylate, and methoxypolyethylene glycol methacrylate; the A2 monomer includes one or more combinations of methyl acrylate, methyl methacrylate, acrylonitrile, methacrylonitrile, styrene, vinyl pyrrolidone, and acrylamide; The crosslinking monomer in step S2 is an olefin monomer containing multiple unsaturated carbon-carbon double bonds, the number of carbon-carbon double bonds is ≥2, and the crosslinking monomer is a combination of one or more of 1,6-hexanediol diacrylate, ethylene oxide diacrylate, ethoxylated bisphenol A diacrylate, polyethylene glycol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate and propoxylated glycerol triacrylate; The B1 monomer in step S3 includes a combination of one or more of acrylonitrile, methacrylonitrile, styrene and vinyl pyrrolidone; the B2 monomer consists of 5 to 100 carbon atoms and other heteroatoms, and includes a combination of one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl methacrylate, isodecyl methylpropionate, amyl acrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, ethoxyphenol acrylate, ethoxynonylphenol acrylate, tetrahydrofurfuryl acrylate, tetrahydrofurfuryl methacrylate, diethylene glycol monoethyl ether acrylate, and methoxypolyethylene glycol methacrylate; The functional monomer in step S3 is a combination of one or more of acrylic acid, sodium acrylate, lithium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, β-acryloxypropionic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium allyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.

2. The fluorine-free binder for lithium ion battery positive electrode according to claim 1, characterized in that: The emulsifier in step S1 is a combination of one or more of calcium dodecyl benzoate, sodium dodecyl sulfonate, sodium dodecyl sulfate, SR-10, SE-10, SN-10 and OP-10; In parts by mass, the amount of A1 monomer added in step S1 is 25-75 parts, the amount of A2 monomer added is 25-50 parts, the amount of cross-linking monomer added is 2-5 parts, the amount of emulsifier added is 0.5%-2.5% of the sum of the mass parts of A1 monomer, A2 monomer and cross-linking monomer, and the amount of initiator added is 0.5%-2% of the sum of the mass parts of A1 monomer, A2 monomer and cross-linking monomer; the amount of deionized water is 4-9 times the sum of the mass parts of A1 monomer, A2 monomer and cross-linking monomer; the pre-emulsification time in step S1 is 30min-50min; In step S1, the mixture is heated to 55-85° C. with stirring and reacted for 2-6 hours. The particle size of the first core emulsion is 20-500 nm.

3. The fluorine-free binder for lithium ion battery positive electrode according to claim 1, characterized in that: The amount of the cross-linking monomer added in step S2 is 5-10 parts, and the initiator in step S2 is 0.5%-2% of the amount of the cross-linking monomer used; after the dropwise addition in step S2, the mixture is stirred and heated to 55-85° C. and reacted for 2-6 hours, and the particle size D50 of the second core emulsion is 20-510 nm.

4. The fluorine-free binder for lithium ion battery positive electrode according to claim 1, characterized in that: The initiator is a combination of one or more of sodium persulfate, potassium persulfate, ammonium persulfate and azobisisobutylamidine hydrochloride.

5. The fluorine-free binder for lithium ion battery positive electrode according to claim 1, characterized in that: The dropping time in step S4 is 0.3h~2h, the insulation reaction is 55℃~85℃, and the reaction time is 1h~8h; the filtration in step S5 is filtering through a 200-mesh filter bag.

6. A positive electrode for a lithium ion battery, characterized in that: The lithium ion battery positive electrode comprises the lithium ion battery positive electrode non-fluorine binder according to any one of claims 1 to 5, and further comprises a current collector and a positive electrode active coating coated on the surface of the current collector.

7. A lithium-ion soft-pack battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery positive electrode as claimed in claim 6.